5.20.34 Problems 3301 to 3400

Table 5.973: Second or higher order ODE with constant coefficients

#

ODE

Mathematica

Maple

17568

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

17571

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

17572

\[ {}a y^{\prime \prime }+b y^{\prime }+c y = 0 \]

17583

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 0 \]

17584

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

17585

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

17586

\[ {}9 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

17587

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

17588

\[ {}y^{\prime \prime }-2 y^{\prime }+6 y = 0 \]

17589

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

17590

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = 0 \]

17591

\[ {}6 y^{\prime \prime }-y^{\prime }-y = 0 \]

17592

\[ {}9 y^{\prime \prime }+12 y^{\prime }+4 y = 0 \]

17593

\[ {}y^{\prime \prime }+2 y^{\prime }-8 y = 0 \]

17594

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

17595

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

17596

\[ {}4 y^{\prime \prime }-9 y = 0 \]

17597

\[ {}25 y^{\prime \prime }-20 y^{\prime }+4 y = 0 \]

17598

\[ {}y^{\prime \prime }-4 y^{\prime }+16 y = 0 \]

17599

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

17600

\[ {}y^{\prime \prime }+2 y^{\prime }+\frac {5 y}{4} = 0 \]

17601

\[ {}y^{\prime \prime }-9 y^{\prime }+9 y = 0 \]

17602

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

17603

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

17604

\[ {}9 y^{\prime \prime }-24 y^{\prime }+16 y = 0 \]

17605

\[ {}4 y^{\prime \prime }+9 y = 0 \]

17606

\[ {}4 y^{\prime \prime }+9 y^{\prime }-9 y = 0 \]

17607

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

17608

\[ {}y^{\prime \prime }+4 y^{\prime }+\frac {25 y}{4} = 0 \]

17609

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

17610

\[ {}y^{\prime \prime }+16 y = 0 \]

17611

\[ {}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0 \]

17612

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

17613

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

17614

\[ {}6 y^{\prime \prime }-5 y^{\prime }+y = 0 \]

17615

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

17616

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

17617

\[ {}y^{\prime \prime }+3 y^{\prime } = 0 \]

17618

\[ {}y^{\prime \prime }+y = 0 \]

17619

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

17620

\[ {}y^{\prime \prime }+6 y^{\prime }+3 y = 0 \]

17621

\[ {}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0 \]

17622

\[ {}2 y^{\prime \prime }+y^{\prime }-4 y = 0 \]

17623

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

17624

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

17625

\[ {}4 y^{\prime \prime }-y = 0 \]

17639

\[ {}y^{\prime \prime }+2 y = 0 \]

17640

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{4}+2 y = 0 \]

17641

\[ {}m y^{\prime \prime }+k y = 0 \]

17642

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 3 \,{\mathrm e}^{2 t} \]

17643

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \sin \left (2 t \right ) \]

17644

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = -3 t \,{\mathrm e}^{-t} \]

17645

\[ {}y^{\prime \prime }+2 y^{\prime } = 3+4 \sin \left (2 t \right ) \]

17646

\[ {}y^{\prime \prime }+9 y = {\mathrm e}^{3 t} t^{2}+6 \]

17647

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 \,{\mathrm e}^{-t} \]

17648

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = 2 \,{\mathrm e}^{t} \]

17649

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 2 \,{\mathrm e}^{-t} \]

17650

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{-t} \]

17651

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 16 \,{\mathrm e}^{\frac {t}{2}} \]

17652

\[ {}2 y^{\prime \prime }+3 y^{\prime }+y = t^{2}+3 \sin \left (t \right ) \]

17653

\[ {}y^{\prime \prime }+y = 3 \sin \left (2 t \right )+t \cos \left (2 t \right ) \]

17654

\[ {}u^{\prime \prime }+w_{0}^{2} u = \cos \left (w t \right ) \]

17655

\[ {}y^{\prime \prime }+y^{\prime }+4 y = 2 \sinh \left (t \right ) \]

17656

\[ {}y^{\prime \prime }-y^{\prime }-2 y = \cosh \left (2 t \right ) \]

17657

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 2 t \]

17658

\[ {}y^{\prime \prime }+4 y = t^{2}+3 \,{\mathrm e}^{t} \]

17659

\[ {}y^{\prime \prime }-2 y^{\prime }+y = t \,{\mathrm e}^{t}+4 \]

17660

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 3 t \,{\mathrm e}^{2 t} \]

17661

\[ {}y^{\prime \prime }+4 y = 3 \sin \left (2 t \right ) \]

17662

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 4 \,{\mathrm e}^{-t} \cos \left (2 t \right ) \]

17663

\[ {}y^{\prime \prime }+3 y^{\prime } = 2 t^{4}+t^{2} {\mathrm e}^{-3 t}+\sin \left (3 t \right ) \]

17664

\[ {}y^{\prime \prime }+y = t \left (\sin \left (t \right )+1\right ) \]

17665

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{t} \cos \left (2 t \right )+{\mathrm e}^{2 t} \left (3 t +4\right ) \sin \left (t \right ) \]

17666

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 3 \,{\mathrm e}^{-t}+2 \,{\mathrm e}^{-t} \cos \left (t \right )+4 \,{\mathrm e}^{-t} t^{2} \sin \left (t \right ) \]

17667

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 2 t^{2}+4 t \,{\mathrm e}^{2 t}+t \sin \left (2 t \right ) \]

17668

\[ {}y^{\prime \prime }+4 y = t^{2} \sin \left (2 t \right )+\left (6 t +7\right ) \cos \left (2 t \right ) \]

17669

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{t} \left (t^{2}+1\right ) \sin \left (2 t \right )+3 \,{\mathrm e}^{-t} \cos \left (t \right )+4 \,{\mathrm e}^{t} \]

17670

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 3 t \,{\mathrm e}^{-t} \cos \left (2 t \right )-2 t \,{\mathrm e}^{-2 t} \cos \left (t \right ) \]

17671

\[ {}y^{\prime \prime }-3 y^{\prime }-4 y = 2 \,{\mathrm e}^{-t} \]

17676

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} t & 0\le t \le \pi \\ \pi \,{\mathrm e}^{-t +\pi } & \pi <t \end {array}\right . \]

17677

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = \left \{\begin {array}{cc} 1 & 0\le t \le \frac {\pi }{2} \\ 0 & \frac {\pi }{2}<t \end {array}\right . \]

17678

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} A t & 0\le t \le \pi \\ A \left (2 \pi -t \right ) & \pi <t \le 2 \pi \\ 0 & 2 \pi <t \end {array}\right . \]

17679

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{4}+2 y = 2 \cos \left (w t \right ) \]

17680

\[ {}y^{\prime \prime }+y = 2 \cos \left (w t \right ) \]

17681

\[ {}y^{\prime \prime }+y = 3 \cos \left (w t \right ) \]

17682

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (\frac {t}{4}\right ) \]

17683

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (2 t \right ) \]

17684

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (6 t \right ) \]

17687

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 2 \,{\mathrm e}^{t} \]

17688

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 2 \,{\mathrm e}^{-t} \]

17689

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{-t} \]

17690

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 16 \,{\mathrm e}^{\frac {t}{2}} \]

17691

\[ {}y^{\prime \prime }+y = \tan \left (t \right ) \]

17692

\[ {}y^{\prime \prime }+4 y = 3 \sec \left (2 t \right )^{2} \]

17693

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{2 t}}{t^{2}} \]

17694

\[ {}y^{\prime \prime }+4 y = 2 \csc \left (\frac {t}{2}\right ) \]

17695

\[ {}4 y^{\prime \prime }+y = 2 \sec \left (2 t \right ) \]

17696

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{t}}{t^{2}+1} \]

17697

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = g \left (t \right ) \]

17698

\[ {}y^{\prime \prime }+4 y = g \left (t \right ) \]